Deteksi Molekuler Gen Fusion (F) dan Analisis Perbandingan Beberapa Enzim Restriksi sebagai Penentu Patotipe Virus Newcastle Disease - Medania Purwaningrum; Verawati Verawati; Aris Haryanto (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Newcastle disease (ND) is a contagious viral disease caused by Avian Paramyxovirus Serotype-1 (APMV-1). This viral infection is responsible for devastating outbreak by attacking nerve, respiration, and also digestive system. This disease often followed with decreasing of eggs production and also responsible for economic losses in the poultry industries around the globe. The main goal was to differentiate virulent or avirulent strain of ND virus from F gene, which is the virulent marker of ND virus, by Reverse Transcription Polymerase Chain Reaction (RT-PCR) and Restrion Enzyme Analysis using BamH1, Hin 1l, and Apa 1. Ten ND virus samples came from Animal Disease Investigation Center (ADIC) Wates virus collection, collected from field case in 2012-2013. Newcastle disease virus was collected by extraction from the samples. The RNA product of extraction were used as a template for amplification in RT-PCR. The target of RT-PCR amplification was F gene. The results indicated positive reaction due to existing of DNA fragment band in size of 767 bp. RT-PCR and Restrion Enzyme Analysis can be used as tool to determine the pathotype of ND virus showed different restriction visualized by gel agarose electrophoresis.